EFFECT OF LIME APPLICATION ON INDIGENOUS NITROGEN-FIXING BACTERIA IN TIDAL SOILS MANAGED FOR THAN 30 YEARS - Ridwan, Rahmawati; Budianta, Dedik; Widjajanti, Hary (BIOVALENTIA: Biological Research Journal, 2017)
The study was conducted to determine the effect of land typology and lime on the population of indigenous nitrogen-fixing bacteria and soil pH, and to analyze the effect of soil typology interaction and lime on the population of indigenous nitrogen-fixing bacteria and soil pH. Sampling of soil in tidal land of Mulya Sari and Banyu Urip Village of Banyuasin Regency, South Sumatera. Then the sample was studied at the Laboratory of Microbiology, Department of Biology, Faculty of Mathematics and Natural Sciences, University of Sriwijaya, Inderalaya. During January-May 2017. Based on the results of the study known the soil typology of the total population of nitrogen-fixing bacteria, the highest population of nitrogen inhibitor bacteria in the second week of soil typology D was 6.0x107 and the highest pH of 5.18 in typology B on week Third, the lime treatment that affected the population of indigenous nitrogen-fixing bacteria, obtained the population of bacteria as much as 9.3x105 in the second week and the highest soil pH 4.93 in the second week, while the results of the interaction between soil typology and lime treatment only affect the population of bacterial inhibitor Indigenous nitrogen, with bacterial population of 3.5x107 in soil typology D in the second week, but this interaction did not significantly affect soil pH, with the highest pH measurement of 5.33 on the soil typology D.Keywords: nitrogen-fixing bacteria, tidal land, lime treatment